1991
DOI: 10.1007/bf01912809
|View full text |Cite
|
Sign up to set email alerts
|

Thermal diffusivity and thermal conductivity studies on the zirconate, cerate and uranate of barium

Abstract: The thermal diffusivity and thermal conductivity of the zirconate, cerate and uranate of barium were investigated by employing the laser flash technique. The variation in the thermal resistivity as a function of temperature was examined and the heat transport behaviour of these materials is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Equation (11) infers that (i) a plot of the inverse of thermal conductivity obtained from the simulation versus the inverse of simulation length should be linear (figures 8), and (ii) the thermal conductivity at the bulk state, κ bulk , can be obtained as the inverse of the y-intercept of the graph. The thermal conductivity with correction made for the finite size effects is shown in figure 9, together with the experimental data [1][2][3]. The simulation result demonstrates a descending trend from 4.26 W m −1 K −1 at room temperature to 2.72 W m −1 K −1 at 2000 K. Our result matches very well with the experimental values obtained from Vassen et al [1].…”
Section: Thermal Conductivitysupporting
confidence: 86%
See 1 more Smart Citation
“…Equation (11) infers that (i) a plot of the inverse of thermal conductivity obtained from the simulation versus the inverse of simulation length should be linear (figures 8), and (ii) the thermal conductivity at the bulk state, κ bulk , can be obtained as the inverse of the y-intercept of the graph. The thermal conductivity with correction made for the finite size effects is shown in figure 9, together with the experimental data [1][2][3]. The simulation result demonstrates a descending trend from 4.26 W m −1 K −1 at room temperature to 2.72 W m −1 K −1 at 2000 K. Our result matches very well with the experimental values obtained from Vassen et al [1].…”
Section: Thermal Conductivitysupporting
confidence: 86%
“…Barium zirconate, BaZrO 3 , which possesses a cubic structure with a lattice constant of 4.192 Å at room temperature, is one of the most useful ceramic materials. This perovskite-structured material attracts a great deal of interest due to its comprehensive applications, among other things, in thermal barrier coatings [1], nuclear fuel [2], refractory [3] and protonic ceramic fuel cells [4]. Therefore, it is important to understand the material's physical properties and stability at high temperatures and high pressures.…”
Section: Introductionmentioning
confidence: 99%
“…However, attention has not been given so far to their thermal transport properties. In an earlier study, Srirama Murti and Krishnaia [11] showed that the thermal conductivity of SrUO 4 is much less than that of UO 2 . Since there is no thermal conductivity data available for these uranates, we have carried out a systematic study of the thermal conductivity of different uranates in the temperature range of 300-1100 K and the results have been analyzed to identify the mode of heat conduction in them.…”
Section: Introductionmentioning
confidence: 97%